Treatment of sarcoidosis-associated pulmonary hypertension: A single centre retrospective experience using targeted therapies - Keir, Gregory John; Walsh, Simon L.F.; Gatzoulis, Michael A; Marino, Philip S; Dimopoulos, Konstantinos; Alonso, Rafael; Raposeiras-Roubin, Sergio; Renzoni, Elisabetta A; Maher, Toby M; Wells, Athol U; Wort, S. John (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Background: Pulmonary hypertension (PH), an increasingly recognised complication of pulmonary sarcoidosis, is associated with increased morbidity and mortality Evidence of benefit with targeted therapies in sarcoidosis associated pulmonary hypertension (SAPH) is limited. Methods: We conducted a retrospective review of patients with sarcoidosis and right heart catheter proven PH who received treatment with targeted therapies (phosphodiesterase-5 inhibitors, endothelin receptor antagonists, or combination) at our hospital. Six minute walk test (6MWT), World Health Organisation (WHO) functional class, echocardiography, pulmonary function test (PFT) and serum brain natriuretic peptide (BNP) data were collected at baseline and during follow-up. Results: Thirty-three patients (16 men) with a mean age of 55.5 ± 10.7 years and mean pulmonary artery pressure of 44.0 ± 8.6 mm Hg received treatment with targeted PH therapies  (sildenafil=29, bosentan=4). At six months, median six minute walk distance improved from 227 (88-526) meters to 240 (140-380) metres (p=0.04), median serum BNP levels improved from 35 (2-424) pmol/L to 26 (4-255) pmol/L (p